2020
DOI: 10.1016/j.molcel.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analyses Reveal Megakaryocyte-Biased Hematopoiesis in Myelofibrosis and Identify Mutant Clone-Specific Targets

Abstract: Highlights d Single-cell-omics demonstrate megakaryocyte-biased hematopoiesis in myelofibrosis (MF) d Megakaryocyte progenitors (MkPs) show high expression of a fibrosis signature in MF d MkPs are heterogeneous in MF with aberrant metabolic and inflammatory signatures d Targeting aberrant surface G6B expression may selectively ablate the MF clone

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(147 citation statements)
references
References 89 publications
6
139
2
Order By: Relevance
“…In addition to modifying HSC proliferation dynamics, the JAK2-V617F mutation also impacts the differentiation dynamics of their progenies. We found that the hematopoietic differentiation hierarchy is largely preserved in ET and PV patients, in contrast to recent observations of aberrant megakaryopoiesis in patients with MF 23 . However, JAK2-mutated HSPCs showed a lineage bias towards the megakaryocyte-erythroid fate and strikingly, we found that the fraction of JAK2mutated cells varied significantly across different progenitor cell populations, suggesting that peripheral blood monitoring may not accurately assess JAK2 mutation burden.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition to modifying HSC proliferation dynamics, the JAK2-V617F mutation also impacts the differentiation dynamics of their progenies. We found that the hematopoietic differentiation hierarchy is largely preserved in ET and PV patients, in contrast to recent observations of aberrant megakaryopoiesis in patients with MF 23 . However, JAK2-mutated HSPCs showed a lineage bias towards the megakaryocyte-erythroid fate and strikingly, we found that the fraction of JAK2mutated cells varied significantly across different progenitor cell populations, suggesting that peripheral blood monitoring may not accurately assess JAK2 mutation burden.…”
Section: Discussioncontrasting
confidence: 99%
“…Using this approach, we detected the JAK2 mutation site (locus encoding codon 617) in at least one transcript in 5-15% of cells (mean 9.5%) in the 7 patient libraries, improving over the existing methods for detecting somatic mutations in single-cell libraries 22,23 . We designated cells in which at least one mutated JAK2 transcript was detected as JAK2-mutant cells.…”
Section: Jak2-mutant Hspcs Exhibit Fate Biasmentioning
confidence: 99%
“…Recent advances in single-cell approaches have uncovered MPN-specific lineage-trajectories and transcriptional programs. In a recent study Psaila et al combined single-cell RNA sequencing (scRNA-seq) with targeted single-cell mutational analysis on the same MPN cell (TARGET-seq) in MF ( 23 ). They found that JAK2 -mutant MF HSPCs are biased toward the megakaryocyte-lineage from an early HSC stage, where megakaryocytic surface markers (e.g., CD41) are absent ( 23 ).…”
Section: Cellular Contributors To Inflammationmentioning
confidence: 99%
“…In a recent study Psaila et al combined single-cell RNA sequencing (scRNA-seq) with targeted single-cell mutational analysis on the same MPN cell (TARGET-seq) in MF ( 23 ). They found that JAK2 -mutant MF HSPCs are biased toward the megakaryocyte-lineage from an early HSC stage, where megakaryocytic surface markers (e.g., CD41) are absent ( 23 ). In an earlier paper, Nam et al also linked genotyping of expressed genes to their transcriptional profile [Genotyping of Transcriptomes (GoT)] ( 24 ).…”
Section: Cellular Contributors To Inflammationmentioning
confidence: 99%
See 1 more Smart Citation